Yield curve inversions: A study of country‐level and firm‐level stock reactions. (7th February 2021) - Quinn, Mitchell D.; Zhang, Lei; Mi, Lin
Abstract: We examine the short‐term stock reactions to yield curve inversions. Our country‐level analysis reveals that including the United States, only 13 out of 41 countries exhibit significantly negative stock returns when yield curves invert. Hence, while inverted yield curves act as a negative signal in some countries, it is not a ubiquitous rule internationally. Our firm‐level analysis is the first of its kind. We find that company stocks exhibit strong responses with 3‐day cumulative abnormal returns averaging −1.22% globally and − 2.83% for US firms. The results suggest that corporate bond yield curves contain valuable information of firms' future performance.